Fuzzy Anp Method And Internal Business Perspective For Performance Measurement In Determining Strategy SMEs - Yeni Kustiyahningsih; Eza Rahmanita; Jaka Purnama (UNEJ e-Proceeding, 2016)
Suramadu bridge is one of the transport Infrastructures that can provide social and economic growth opportunities, especially in Madura Island. Bangkalan Indonesia district is closest to longest bridge access. The number of SMEs (Small, and Medium Enterprises) in Bangkalan Indonesia reach more than 125 thousand units, it is possible and potential as an engine of regional economic growth as well as a reduction aspects of unemployment and poverty in the future. Therefore, one important factor Influencing the ongoing advancement of SMEs is a performance measurement. Performance measurement in this study is based on a perspective of the Balanced Scorecard is an internal business. Internal business consists of several indicators, namely Variation Batik, Raw Material Price Increase, Weather Conditions, Production, total manpower, the number of new products, Sales Transactions, Ownership (Shop). This indicator is measured using methods FANP (fuzzy analythic network process), while FANP is a comparison matrix phase, conversion to triangular fuzzy number, geometric mean calculation, synthetic extend calculation, determining  the degree of likelihood, determining the weight vector and normalization. This research approach integrated internal business perspective and fuzzy Analytic Network Process (FANP). The results of this research is a priority weighting of assessment indicators of internal business perspective. Based on sensitivity testing, then obtained batik variety of criteria and new product be a major factor in determining the future strategy for batik persisted with emphasis on local knowledge area.